THE EFFECTS OF VISUAL METAPHORS IN ADVERTISEMENT (Proceedings of International Educators Conference, 2024)
A metaphor is a figure of speech in which the meaning of a word or phrase is implied by applying it to something that it does not physically apply to. The information superhighway is the internet, for instance. Our ability to understand and make sense of the world is deeply rooted in metaphors. They are "pervasive in thought and action, as well as language, in everyday life." Our everyday conceptual framework, which guides our thoughts and actions, is essentially metaphorical. Johnson and Lakoff, 1980). Metaphors are widely used in advertising. Seventy-five percent of print ads have a title that uses at least one metaphor, this article highlights the types and impacts of visual metaphors through the advertising texts